Predicting E-government Use in Mauritius: Non-Parametric Procedures - Sanmukhiya, Chintamanee (International Journal of Psychosocial Rehabilitation, 2020)
This study changes the way in which research has so far been conducted on assessing the extent to which the UTAUT model predicts the use of e-government. It also contributes to the theoretical framework by adding up a trust component to forecast behavioural intention. This study adds other factors to the theoretical model such as frequency of use, sector of occupation, education and urbanisation. Instead of merely summing up Likert-type items, this research identifies those individual factors behind all UTAUT components and Trust dimension that predict the use of the Mauritian government website both in the short and long run under the non-parametric approach. Mann-Whitney U tests, Kruskal-Wallis H tests, Bonferroni correction and Jonckheere-Terpstra testsare used throughout the analysis. Data were randomly collected through questionnaires across 221 citizens who use the government website in Mauritius. Factors such as adequate knowledge, self-confidence, convenience of use, support at work, influential people, opinions of valued people, recommendations by important people to use the e-portal, improved job performance, ability to complete task online, having useful and required information online, ease of finding information, trust in government departments and website, online security and non-disclosure of personal details to third party affect a citizen’s intention to continue to use e-government portal in the future. In addition to these factors, having a computer or laptop, and cheap internet subscription affect short term behavioural intention but not long term behavioural intention. The reverse applies for updated information, easy to understand and use, maintain confidentiality, the enactment of laws against cybercrimes and seen as competent by colleagues. Results are significant at 0.1%, 1% and 5% level. Frequency of use and sector of occupation play key roles in influencing a citizen’s desire to use government websites across all UTAUT and Trust components. Urbanisation however does not affect e-government use at all. This study enables policymakers and government website administrators to tackle those aspects that may favourably mould citizens’ perceptions towards the government website. It will thus enhance e-government practice in Mauritius.